Axin 1 knockdown inhibits osteoblastic apoptosis induced by Porphyromonas gingivalis lipopolysaccharide. (April 2020) - Zhang, Ke; He, Shihui; Dai, Zhixiang; Cao, Li; Yue, Shichao; Bai, Yuxing; Zheng, Min
Highlights: Pg-LPS induced osteoblast apoptosis and inhibited cell activity. The effect of Pg-LPS on osteoblasts was concentration and time dependent. Axin 1 knockdown inhibited Pg-LPS-induced osteoblastic apoptosis. Abstract: Background: Porphyromonas gingivalis (Pg) is one of the pathogenic bacteria that cause periodontal diseases, lipopolysaccharide (LPS) is the key factor that triggers alveolar bone absorption. This study explored the action of Axin 1 on Pg-LPS-induced osteoblasts injury, so as to search a possible treatment for periodontal diseases. Methods: Rat osteoblasts were dealt with Pg-LPS and Axin 1 knockdown alone or in combination. The effect of Pg-LPS and Axin 1 on osteoblast viability and apoptosis were detected by Cell Counting Kit-8 and flow cytometry. The expressions of alkaline phosphatase (ALP) and Axin 1 in processed osteoblasts were measured by western blot (WB) and quantitative real-time polymerase chain reaction (qRT-PCR) assays. Furthermore, the role of Axin 1 knockdown in the levels of inflammatory cytokines and apoptosis-related proteins were also determined. Results: Pg-LPS inhibited the viability of osteoblasts and promote apoptosis with concentration and time dependence. ALP expression in Pg-LPS-treated osteoblasts was reduced, while Axin 1 expression was increased. On the one hand, Axin 1 knockdown reversed the Pg-LPS-induced reduction of cell activity and pro-apoptosis effect. On the other hand, Axin 1 knockdown not only improved the ALP activity of Pg-LPS-treated cells, but also reduced the elevation of inflammatory cytokines (TNF-α, IL-1β and IL-6) caused by Pg-LPS. Moreover, Pg-LPS increased the expressions of cleaved Caspase-3 and Bax, and inhibited Bcl-2 expressed, which was rescued by Axin 1 knockdown. Conclusion: Axin 1 knockdown inhibited Pg-LPS-induced osteoblastic apoptosis by regulating the levels of inflammatory cytokines, which may be helpful for the treatment of periodontal diseases.